Comparative Analysis of the Mesh Treating Methods in the Numerical Heat Transfer Calculation of Nonhomogeneous Building Components. Issue 16 (1st November 2016) - Zhang, Yuan; Wang, Geng; Du, Kai; He, Jiapeng
Abstract : Two two-dimensional numerical models for solving the heat transfer problems within no-homogeneousbuilding component s, choosing the interfaces between two layers (Method A) or the thermal property step surfaces (TPSSs) (Method B) as thenode s of computationalmesh es, were compared, A typical hollow building block wall was selected and multiple heat transfer experiments with constant and dynamic temperature conditions have been conducted. The calculation results of the two models both show a reasonable agreement with the experimental data. Furthermore, this demonstrates that there is lower calculation error for Method B than that for Method A, and the factors causing errors for Method A have been analyzed. The calculation error of the Method A decreases with the thermal resistance of the whole structure and the thickness of each layer, but increases with the thermal conductivity difference between the two materials adjacent to TPSS, the thermal capacities of materials, and the number of TPSSs. In addition, for both the two mesh treating methods, small enough mesh step size (≤0.005 m) guarantees high calculation accuracy.